Understanding childfree according to the views of the Indonesian childfree community reviewed from islamic law - Alwi Sipayung, Fakhri; Milhan, Milhan (LP3M Universitas Islam Zainul Hasan Genggong, 2025)
The phenomenon of “Childfree” has gained increasing attention in recent years, as more and more people choose not to have children. This research explores the phenomenon of childless individuals in the Childfree Indonesia community which is studied from their perspective and experiences which are guided by the principles of Islamic law and how women's reproductive rights view Childfree. The study of research methods in this legal research uses an empirical research type, namely legal research that analyzes and examines the workings of law in society. Empirical legal research views law as actual behavior and unwritten social phenomena, experienced by society in everyday life. This research investigates various reasons and how some members of the Childfree Indonesia community respond to choosing not to have children. This has many factors behind it. This includes the desire for personal freedom, economic factors, mental health factors or environmental factors. On this basis, it shows that the decision to remain Childfree is a complex decision and has many aspects, and often requires careful consideration regarding the perceived benefits and impacts. Also included in the perspective of Islamic law, this research analyzes the extent to which the choice to remain Childfree is in line with or deviates from the teachings of Islamic law.